2021
DOI: 10.1007/s00348-021-03186-8
|View full text |Cite
|
Sign up to set email alerts
|

Passive flow control mechanisms with bioinspired flexible blades in cross-flow tidal turbines

Abstract: State-of-the-art technologies for wind and tidal energy exploitation focus mostly on axial turbines. However, cross-flow hydrokinetic tidal turbines possess interesting features, such as higher area-based power density in array installations and shallow water, as well as a generally simpler design. Up to now, the highly unsteady flow conditions and cyclic blade stall have hindered deployment at large scales because of the resulting low single-turbine efficiency and fatigue failure challenges. Concepts exist wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…This deformation mitigates the change in loads sensed by the blades and therefore prolongs the fatigue life of the turbine. The effectiveness in load alleviation of morphing blades has been recently demonstrated [100][101][102]. Hence, it is foreseen that flexible material blades can extend the fatigue life of offshore floating VAWTs.…”
Section: Way Forward To Increase Trlmentioning
confidence: 99%
“…This deformation mitigates the change in loads sensed by the blades and therefore prolongs the fatigue life of the turbine. The effectiveness in load alleviation of morphing blades has been recently demonstrated [100][101][102]. Hence, it is foreseen that flexible material blades can extend the fatigue life of offshore floating VAWTs.…”
Section: Way Forward To Increase Trlmentioning
confidence: 99%
“…The case is inspired by the experimental work of Hoerner et al [6] to show how hyperflexible foils effectively adapt dynamically their shape and passively control the flow through deformation. The case consist to a pitched hydrofoil surrounded by a water stream.…”
Section: Case Presentationmentioning
confidence: 99%
“…However, Hoerner et al [5,6] showed in recent experimental studies that in the operational characteristics of a Vertical Axis Turbine (VAT), blades with high flexibility deliver significantly higher torque and can reduce structural loads, extending turbine lifetime. These potential improvements of turbine efficiency seem to be explained by the influence of the chordwise flexibility on dynamic stall which implies a drag reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Results of Figure 9 show that the oscillating membrane has a higher impact in C D than in C L . Hence oscillating membranes could be complementary to load alleviation technology that modifies C L , for example, passive trailing edge flaps that mitigate peak loading in fluctuating flows [31,47].…”
Section: Frequency Analysismentioning
confidence: 99%